Som e música da ficção científica em quatro obras do cinema brasileiro - Scarpelli, Alexandre Camargo (Universidade Federal de São Carlos, 2020)
This research aims to analyze the role played by sound and music in the filmic discourse of four Brazilian works evaluating their connections to the science fiction universe and paying special attention to the Brazilian iconography of the genre. The selected films are White out, black in (2015) by Adirley Queiroz and the short film Dog days (2016) by Ronaldo Dimer and Vitor Amaro, both evaluated under the theme of political dystopia, as well as the short films Last song for a rude heart, (2017) by Marco Antônio Pereira and Cold Recife, by Kléber Mendonça Filho, understood as satires and evaluated for their representations of alien figures. Genre theory, science fiction studies, film music and film sound theories, as well as Brazilian science fiction studies allow us to first observe and investigate sonic and musical codes created and developed by canonical works of international science fiction cinema, subsequently enabling a shift in perspective that considers the Brazilian context of science fiction films in order to discuss the music and sound design of the selected works.
Sound and music of science fiction in four works of brazilian cinema
Keywords: Ficção científica; Cinema brasileiro; Som; Música fílmica; Science fiction; Brazilian cinema; Film sound; Film music; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO::TEORIA DA COMUNICACAO